Effect of Replaced Partial or Complete Fermented Wheat by Saccharomyces cerevisiae, Probiotic and Rumen Liquor with urea Instead of Corn on Productive Performance of Broiler Chicks - Hammod, Ali Jebr; Mohammed, Abdullah A.; Jassim, Jaffer M. (Journal of Kerbala for Agricultural Sciences, 2018)
As the field experiment designed to study the replacement of wheat fermented with Saccharomyces cerevisiae and Iraqi probiotic and rumen liquor with urea partially or completely replace corn in diets on the productive performance of broiler chickens as well as digest it conducted a second test after the end of the second field experiment. In this experiment, A 450 chicks were used and distributed over 10 treatments each with three replicates (15 chicks for replicate) treatments are: T1 and T2 partial and complete replacing of wheat without urea instead of corn, respectively (controls); T3 and T4 partial and complete replacing of wheat with urea instead of corn, respectively (controls); T5 and T6 partial and complete replacing of wheat fermented by Saccharomyces cerevisiae with urea instead of corn, respectively; T7 and T8 partial and complete replacing of wheat fermented by Iraqi probiotic with urea instead of corn, respectively; T9 and T10 partial and complete replacing of wheat fermented by rumen liquor with urea instead of corn, respectively. The current studies included the following results: The results showed that there were significant increases in final live body weight, total weight gain of T5, and accumulative feed intake for the T6 group, while T10 recorded the best conversion ratio, also T9 and T10 recorded the best economic figure.